KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL LITERASI NUMERASI DENGAN KONTEKS BUDAYA MINANGKABAU - Fadillah Turahmi; Isnaniah; Wedra Aprison; M.Imamuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by observations at SMP N 1 Padang Panjang, which showed students' low mathematical problem-solving abilities in solving numeracy literacy problems within the Minangkabau cultural context. These observations were reinforced through interviews with mathematics teachers, who revealed that students were accustomed to solving simple problems, thus experiencing difficulties when faced with problems with higher levels of difficulty. This condition impacted students' critical mathematical problem-solving skills in culturally relevant contexts. This study aimed to describe the mathematical problem-solving abilities of grade IX.D students at SMP N 1 Padang Panjang in solving numeracy literacy problems based on Minangkabau culture. This study used a quantitative descriptive approach, with subjects selected through purposive sampling. The research instrument consisted of five numeracy literacy essay questions that assessed mathematical problem-solving abilities. Data analysis was conducted by calculating scores, determining ability categories, calculating the average percentage per indicator, and presenting an overall picture of students' mathematical problem-solving abilities. The results showed that students' overall mathematical problem-solving abilities were low, with an average percentage of 41.75%. Based on indicators, ability is in the low category for the first indicator (44.37%), second indicator (52.29%), and fourth indicator (5.31%), while the third indicator is in the medium category (65%).